Age, Death Risk, and the Design of an Exit Strategy: A Guide for Policymakers and for Citizens Who Want to Stay Alive - Andrew J. Oswald; Nattavudh Powdthavee (Institute of Labor Economics (IZA), 2020)
Some commentators argue for a fairly general release from COVID-19 lockdown. That has a troubling flaw. It ignores the fatality risks that will then be faced by citizens in midlife and older. This paper provides information on the strong age-pattern in the risk of death from three countries (China, Italy, the UK). If politicians want an imminent removal of the lockdown, the safest approach in our judgment would be a rolling age-release strategy combined with the current principle of social distancing. But even if that is not the policy adopted, citizens need to be shown graphs of the kind in this paper. Honest guidance ought to be given to those in midlife and beyond. Governments have to allow people to understand their personal risk after any release from lockdown.
Keywords: I18; J13; K38; H75; 330; coronavirus; labor market; recession; COVID-19